If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = -25x + 9 Reorder the terms: 0 = 9 + -25x Solving 0 = 9 + -25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '25x' to each side of the equation. 0 + 25x = 9 + -25x + 25x Remove the zero: 25x = 9 + -25x + 25x Combine like terms: -25x + 25x = 0 25x = 9 + 0 25x = 9 Divide each side by '25'. x = 0.36 Simplifying x = 0.36
| 4n=368 | | 7(x-1)=11.2 | | =5x-3[(11x-5)-(x-2)] | | 3-2(a-1)=4a-13 | | 5.2=2c-9 | | z^2+2iz-3i=0 | | 4(x-2)+12=2(5-2x) | | 20+X=51 | | 6e-8=16 | | -y+7(6+2y)= | | 2x+12=68+6x | | 5x+2y^2=3 | | (h-78)/9(1)+(-13)+50-(78*.25)=-20 | | 4(2x-1)=-28 | | 4(x-8)=0 | | 22=t | | 8+1.25=16.75 | | 3x+38=16+x | | 184+2h=986 | | x+3x-1+x+15= | | 3x^2-6x+11000=0 | | 4x(x)=49 | | 2x^6*x-95=0 | | 0.2p-10= | | 6-4x=x+7(x+8) | | 144=16t | | 28(p+30)=3,108 | | 8.32+7.76-10.09= | | 3,108=28(p+30) | | x+(3x+4)=112 | | 6(2x-3)=24 | | X+(x-21)=157 |